The transformation is a reflection in the line [tex]y=x [/tex] followed by a reflection in the line [tex]x=1 [/tex] .
The mapping for a reflection in the line [tex]y=x [/tex] is [tex](x,y) \rightarrow (y,x) [/tex] .
That is simply swapping the coordinates.
[tex]A(-3,4) \rightarrow (4,-3) [/tex]
[tex]B(-3,0) \rightarrow (0,3) [/tex]
[tex]C(-1,3) \rightarrow (3,-1) [/tex]
Now we reflect the resulting coordinates in the line [tex]x=1 [/tex] which has the mapping [tex](x,y) \rightarrow (2(1)-x,y) [/tex]
So we transform the resulting coordinates as follows:
[tex](4,-3) \rightarrow A'(2(1)-4,-3) [/tex]
[tex](0,-3) \rightarrow B'(2(1)-0,-3) [/tex]
[tex](3,-1) \rightarrow C'(2(1)-3,-1) [/tex]
Hence we have
[tex]A'(-2,-3),B'(2,-3) \: and\: C'(-1,-1) [/tex]